Implementation of Sustainable Development Goals (SDGS) in the Kkn-Pmm Real Action Collaboration Program at Warmadewa University in Darmasaba Village, Abiansemal District, Badung Regency - Sugiantiningsih, Anak Agung Putu (Abdi Masyarakat, 2025)
This research is a further study in facing the complexity of challenges related to the achievement of the Sustainable Development Goals (SDGs), especially in the environmental sector in Darmasaba Village. In the face of increasingly complex global and national dynamics, a deep understanding of environmental issues is very important in formulating effective policies in every decision-making. By collaborating on the KKN work program carried out in Darmasaba Village. This research specifically emphasizes the role of KKN students who focus on work programs that increase public awareness both in protecting the environment, improving human resources, and making Darmasaba Village a village with integrity. With the work program that has been implemented, it is hoped that it can realize collaborative efforts that are more efficient, sustainable and achieve goals.